Ferula ammoniacum gum aqueous extract exerts anti-inflammatory and antioxidant mechanisms to combat aluminum chloride-induced Alzheimer’s disease in rats: possible involvement of opioid pathways - Fakhri, Sajad; Gravandi, Mohammad Mehdi; Majnooni, Mohammad Bagher; Farzaei, Mohammad Hosein; Abbaszadeh, Fatemeh; Rashidi, Khodabakhsh; Echeverría, Javier (Frontiers in Pharmacology, 2026)
BackgroundAlzheimer’s disease (AD), the most common form of dementia, significantly affects memory and behavior due to dysregulated pathways involving oxidative stress, inflammation, and opioidergic systems. Currently, no effective treatments are available, underscoring the need for novel alternatives. Ferula ammoniacum (D.Don) Spalik, M. Panahi, Piwczyński, and Puchałka [Apiaceae] (FA), an Iranian medicinal plant, is known for its anti-seizure, anti-inflammatory, and analgesic properties, with its gum utilized as a nerve tonic.PurposeThis study investigates the anti-AD effects of F. ammoniacum gum aqueous extract (FAGAE) using an aluminum chloride (AlCl3)-induced Wistar rat model of AD.Materials and methodsThe aqueous extract, prepared by macerating powdered gum in distilled water for 48 h at ambient temperature, was subjected to phytochemical analysis using ultraviolet, infrared, and nuclear magnetic resonance spectroscopy. Thirty rats were assigned to five different groups: one receiving saline, one receiving AlCl3 (100 mg/kg, i.p.), two receiving AlCl3 followed by oral treatment with FAGAE at doses of 50 or 100 mg/kg, and one receiving naloxone (an opioid receptor antagonist) along with AlCl3 and the effective dose of FAGAE. Behavioral changes were evaluated using the open-field, passive avoidance, and elevated plus maze tests. Furthermore, biochemical analyses were conducted to measure the serum nitrite levels, changes in weight, matrix metalloproteinase (MMP) activity, and histopathological changes in brain tissue.Results and discussionThe phytochemical analysis of FAGAE revealed the presence of polysaccharide compounds with tentative arabinogalactan structures. FAGAE decreased step-through latency in the passive avoidance test and modified AlCl3-induced weight changes. FAGAE also significantly increased mobility, grooming, and crossing in the open-field test. Naloxone reversed the anti-AD effects of FAGAE, suggesting a possible role for opioidergic pathways in its therapeutic effects. Zymography results showed that FAGAE reduced MMP-9 activity while increasing MMP-2 activity. Histopathological analysis revealed a preserved number of intact neurons in the hippocampus, whereas reduced serum nitrite levels were observed after FAGAE administration in rats with AD.ConclusionBehavioral, biochemical, and histopathological impairments induced by AlCl3 were significantly attenuated by FAGAE, possibly through the opioidergic pathway, which combats inflammation and oxidative stress and supports neuronal survival.